Peran Masyarakat Dalam Pendidikan perspektif Pendidikan Islam - Sada, Heru Juabdin (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2017)
Education is a shared responsibility starting from the government, parents, then the community. Society plays a very important role in the development of children's education. Therefore, the community should participate in participating in children's education activities either directly or indirectly. The implementation of education itself will certainly have an impact on the community itself, thus there is a positive correlation between society and education. The better education is held, the better will be the quality of the community. Vice versa, the better the quality and the better the community, the better and better quality of education held. Therefore, community education must receive serious attention in the system of implementing Islamic education. The results of this study found that the role of the community in Islamic education can improve quality and superior management.